Review of Alyn Shipton. 2001. A New History of Jazz. London and New York: Continuum - Tirro, Frank (Current Musicology, 2001)
The arrival of a book that purports to be a “new” history of jazz signals an event of no small consequence among the dedicated community of jazz scholars. Several excellent histories, such as those by Lewis Porter and Michael Ullman (1992) and by Ted Gioia (1997), have been published within the past decade, the former a work of careful scholarship and good pedagogical sensibility and the latter just as thoughtfully constructed, but more philosophical in nature. At the same time, outstanding dissertations, monographs, research articles, collected readings, conference papers, reviews, obituaries, discographies, useful web sites, and more are now appearing with frequent regularity to expand our knowledge of the field. Barry Kernfeld’s finely edited second edition of the New Grove Dictionary of Jazz (2001), popularly referred to as JazzGrove II, is a stellar resource and has been welcomed with consistently good reviews. Additionally, the hundreds of entries onjazz, ragtime, blues, and popular musicians in the new American National Biography (Garraty and Carnes 1999) have begun to give us a sense of finally coming to grips with the history of this music. In dealing with Shipton’s book, we must first put the publisher’s hyperbole to rest and hope that it does not truly represent the view of the author. To start with, the book is accompanied by a pair of compact disk recordings entitled: Jazz: The Definitive Performances. Almost by definition, there are no definitive performances in jazz, an improvisatory art that reinvents the created art object with each subsequent performance. Also, no collection of thirty-two samples can even approach a representative display of jazz in its many forms or its artists in their various phases. Additionally, any collection of jazz that has no Charlie Parker recordings, for whatever reason, is certainly less than definitive. And finally, compared to the outstanding list of jazz recordings selected by Martin Williams for the Smithsonian Collection of Classic Jazz-even with its faults, omissions, and limitations-Shipton’s two CDs are not in the same league. The publisher’s press releases also billed this book as an “antidote to Ken Burns’ ‘Jazz’,” the ten-part television documentary that needs no antidote. Burns’s work, with all its shortcomings, was constructed in a totally different medium, created with a substantially different audience in mind, and was part of a larger personal triptych on race relations in the United States: The Civil War, Baseball, and Jazz. The comparison is unwarranted and unfair.